A Model Proposal for Forensic Medical Interview with Women Victims of Domestic Violence - Gök Çatal, Yeşim; Uzunyayla, Zuhal; Ünüvar Göçeoğlu, Ümit; Burcu Ersoy; Balcı, Yasemin (The Bulletin of Legal Medicine, 2024)
Objective: Forensic medical interviews of victims of violence against women constitute an important step in the reporting processes. It is aimed to develop standardize interview for violence against women and to create an interview model. Methods: A prospective study was planned with 80 women between the ages of 18-65 who applied between 2020-2021 after being exposed to physical violence by intimate partners. One-on-one clinical interviews were conducted with the cases and information on sociodemographic characteristics and physical violence were obtained including three generations. Results: The mean age was 35.3 years, the mean age of intimate partners was 39 years. In 66.3% of the cases, the duration of exposure to violence is less than 5 years. 95% reported that there was emotional and economic violence with it. 53.8% of the cases were exposed to violence in their childhood, 41.3% of them witnessed violence between their parents. 63.7% of the women inflict violence on their children. Psychiatric referral was made in 40%, 71.9% of those who received psychiatric support stated that this support was good for them. Conclusion: Violence against women is a serious public health problem faced by all healthcare professionals, especially forensic medicine specialists. A standardized clinical interview with the surviwors of violence; will be able to evaluation processes such as a checklist. With the results of this study, a standardized interview model has been developed.